Functional screening of a human saliva metagenomic DNA reveal novel resistance genes against sodium hypochlorite and chlorhexidine - Johannes Wigand; Supathep Tansirichaiya; Endre Winje; Mohammed Al-Haroni (BMC, 2021)
Abstract Objective Many sections of the health care system are facing a major challenge making infectious disease problematic to treat; antimicrobial resistance (AMR). Identification and surveillance of the resistome have been highlighted as one of the strategies to overcome the problem. This study aimed to screen for AMR genes in an oral microbiota, a complex microbial system continuously exposed to antimicrobial agents commonly used in dental practice. Materials and methods As a significant part of the oral microbiome cannot be conventionally cultured, a functional metagenomic approach was chosen. The human oral metagenomic DNA was extracted from saliva samples collected from 50 healthy volunteers in Norway. The oral metagenomic library was then constructed by ligating partially digested oral metagenome into pSMART BAC vector and introducing into Escherichia coli. The library was screened against antimicrobials in dental practices. All resistant clones were selected and analyzed. Results Screening of the oral metagenomic library against different antimicrobials detected multiple clones with resistance against chlorhexidine, triclosan, erythromycin, tetracycline, and sodium hypochlorite. Bioinformatic analysis revealed both already known resistance genes, including msr, mef(A), tetAB(46), and fabK, and genes that were not previously described to confer resistance, including recA and accB conferring resistance to sodium hypochlorite and chlorhexidine, respectively. Conclusion Multiple clones conferring resistance to antimicrobials commonly used in dental practices were detected, containing known and novel resistant genes by functional-based metagenomics. There is a need for more studies to increase our knowledge in the field.